Assessment of changes in the upper airway in children with finger sucking habit using cephalometric radiographs - Sharmila Priyanka Betha; Bushra Kanwal; Randhir Kumar; Disha Jandial; Rabab Musalli; Praveen Kumar Varma (Wolters Kluwer Medknow Publications, 2023)
Introduction: The persistence of the sucking beyond a certain age has been attributed to many deleterious effects on the orofacial structures. Hence, the present study evaluates the alterations in the upper airway among the children with and without the finger-sucking habits. Material and Methods: We piloted an observational study among 58 children with malocclusion who required orthodontic treatment, in which between 7 and 12 years were selected. They were subjected to lateral cephalometric radiographs, and cephalometric analysis of craniofacial morphology, tongue posture, hyoid bone position, upper airway, and head posture was performed and analyzed using independent t-test. Results: In the children with finger-sucking habit group, not only the maxilla was placed anteriorly in relation to the cranial base, but also increased Abstract xi in the length of the palate and the tongue posture. No significant alterations were seen in other parameters. Conclusion: Changes were evident among the children with finger-sucking habits for the craniofacial morphology, tongue posture, upper airway, and head posture with no alteration in the hyoid bone position.